Sosialisasi Parenting Peluk Tumbuh: Cinta Dan Stimulasi Anak Hebat - Amalia, Riska; Mafudhoh, Amanda; Maretta, Evelyna Shafa; Ramadhani, Meisya Citra; Sri Diyanti, Daffa Dwi (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
Parenting is a parenting pattern for children. Parenting comes from two words, namely first, the word “pattern” and second the word “care”. Parenting can be interpreted as a system, way of working or form in an effort to maintain, care for, educate and guide children so that they can stand alone. In addition, parenting can be interpreted as the interaction between children and parents during parenting activites. Character is interpreted as a way of thinking and behaving that is typical of each individual to live and work together, both within the scope of the family, society, nation and state. Individuals with good character are individuals who can make decisions and are ready to be responsible for every consequence of their decisions. From the activites that have been carried out, namely “Socialization of the Importance of Parenting in the Formation of Children’s Character” can increase knowledge, improve understanding and awerness of parents about the importance of parenting science and the impacts caused by errors in parenting patterns in the formation of children’s character.